Population genetic confirmation of species status of the malaria vectors Anopheles willmori and An.pseudowillmori in Thailand and chromosome phylogeny of the Maculatus group of mosquitoes - C. A. GREEN (2018)
Among the Anopheles (Cellia) maculatus group of Oriental mosquitoes, positive assortative mating occurs within sympatric and synchronous populations of An.willmori and An.pseudowillmori in the presence of populations of An.maculatus and An.sawadwongporni, judged from the occurrence of inversion homozygotes and the absence of any heterozygotes in their distinctive, polytene chromosomes. Genotypic frequencies for enzyme electromorphs give additional evidence for the species status of An.pseudowillmori and a practical means of identification in field studies of malaria vectors. Autosomal rearrangements are referred to those of An.stephensi which is unique for 4y. An. willmori differs by a single inversion, 4x; An.pseudowillmori by three Arm 2 inversions; and An.dispar by one Arm 2 inversion and 4x. Fixed autosomal rearrangements in the Maculatus group are summarized and their phylogenetic distribution suggests some unknown, intrinsic mechanism by which genome structure is disrupted in association with speciation events. This could be relevant to the potential genetic manipulation of malaria vectors. Copyright © 1992, Wiley Blackwell. All rights reserved